Silver Nanoparticles AgNPs Preparation by Chemical Method to Obtain Optimal Characteristics of The Pharmaceutical Form and Study Their Effect on The Leishmania Parasite in Laboratory - Sattout, Rama Muhamad; Kamari, Ahmad; Bilal, Muhamad Muayyad (Journal of medical and pharmaceutical sciences, 2021)
This study aimed first to prepare silver nanoparticles AgNPs in a chemical reduction, The silver nanoparticles AgNPs properties were characterized using spectroscopy of Vision and UV- Visible (UV- Vis), and atomic force microscopy (AFM) and a ZetaSizer device. This study also aimed to study the results effect of preparing Silver nanoparticles on the Leishmania parasite using an artificial environment.The results of the spectrophotometer of the secondary silver solution with yellow color, showed maximum absorption at a wavelength of 400 mm, while the image of atomic force microscope (AFM) showed the hierarchical morphology shape of the prepared Silver nanoparticles with an average size of (10- 30 nm). Silver secondary particles were estimated with a diameter ranging from (12- 60 nm) and with good dispersion in water by ZetaSizer device.The results illustrated that the number of Promastigotes of the Leishmania parasite decreased after adding the Silver nanoparticles AgNPs in varying proportions, as the concentration of 500 μg/ml had the highest effect after 72 hours from incubation, and the percentage of remaining parasites was 5.2% comparing with the control percentage of 14.99%, while the value of IC50 was 253.075 μg/ml, The value of R2 = 0.8809, slope = 0.0478 after 24 hours from incubation.
Keywords: AgNO3; AgNPs; Zetasizer; Leishmania